Overview of Corporate Governance Issues for Co-operatives - Shaw, Linda (International Finance Corporation, Washington, DC, 2017)
Good governance is now accepted as vital to achieving the Millennium Development Goals and as a pre-condition for sustainable economic growth. Ensuring better governance of corporations, financial institutions and markets is increasingly recognised for developing countries despite the limited number of firms there with widely traded shares (Oman and Blume 2005). For developing countries, significant benefits can be linked to higher corporate governance standards in the private sector. These include better access to external finance, lower costs of capital and better firm performance (Claessens 2003). The corporate governance agenda has also been broadened by the recognition of the reach of corporate models characterised by different forms and structures to the Anglo-American model of an investor owned firm. However until now little attention has been paid to the governance needs of other institutional forms of business such as co-operatives despite their considerable presence in many developing countries. The co-operative sector as a whole remains poorly understood and its specific governance challenges remain as yet largely unexplored. This aim of this paper is to begin to remedy this absence. Taking as a starting point the distinct nature of co-operatives, relevant trends and issues within corporate governance are explored within the framework of the co-operative sector.